Study on induction hardening performance of 34CrNi3MoA steel crankshaft - Shi, Xiaona; Lv, Chenghao; Li, Guochao; Wang, Kelong; Chen, Jianzhi; Tang, Jie (Frontiers in Materials, 2023)
The evolution of the temperature field, microstructure field, and residual stress field of a 34CrNi3MoA steel marine diesel engine crankshaft during medium-frequency induction hardening was studied based on an electromagnetic-thermal-transformation-stress coupled numerical model, which considers the effect of internal stress induced by transformation induced plasticity on residual stress. Using the equal conversion rate method, the austenitizing region of the crankshaft was determined during the induction heating stage. In the quenching stage, the parameters of the phase transformation model are derived from the continuous heating expansion curve and the continuous cooling transformation curve, and the phase transformation kinetics equation is used to analyze the phase transformation process of the crankshaft. The results indicate that extending the heating time can enhance the uniformity of the surface temperature of the crankshaft and the thickness of the hardened layer. The simulation results are validated by measurements of hardened layer, hardness and residual stress, and the simulation results are in good agreement with the experimental results.